STUDI FENOMENOLOGI PENGALAMAN MERAWAT ANAK DENGAN HIV - Ernawati, Eka; Marwiyah, Nila; Rahmawati, Dewi (Coping: Community of Publishing in Nursing; Vol 10 No 2 (2022): April 2022DO - 10.24843/coping.2022.v10.i02.p11, 2022)
The phenomenon of caring for sick family members is a challenge. Human immunodeficiency virus is a disease that requires handling and support both in prevention, transmission, and treatment. There are still many families who are dishonest in caring for children with HIV. The purpose of this study was to determine the life experiences of families and health workers in caring for children with HIV at Serang Hospital. The research method uses a qualitative research design with phenomenological approach. Participants were taken using purposive sampling. The number of participants involved in 7 families with children with HIV and 6 health workers (2 doctors and 4 nurses). The research instrument is the researcher along with the research members. Data retrieval using interviews with deep interviews. The results of the analysis obtained themes: (1) ignorance of knowing HIV disease when the child is being treated; (2) loss of follow-up related to treatment; (3) barriers to early diagnostic examination; (4) economic demands in the child care. The results of this study can be useful for improving care for children with HIV by increasing public knowledge in collaboration with health workers.